A re-evaluation of Scinaia (Nemaliales, Rhodophyta) in the Azores. - Léon-Cisneros, Karla (2011)
The genus Scinaia in the Azores is re-evaluated based on historical and recent collections. A combination of morphological and anatomical diagnostic characters was used for species segregation, and a key for Azorean species determination is presented. Anatomical information associated to the hair development is described for the first time for the genus. The occurrence of S. furcellata and S. interrupta is confirmed for the archipelago. The presence of S. acuta is reported for the first time in the Azores, representing a spread from Australia to the N-Atlantic and specifically into the Macaronesian region. Its occurrence in the archipelago and the Canaries is discussed as a possible introduction.